Computer Communications / Principles and Business Applications - Sloane Andy (Mcgraw Hill Book Company, 1994)
A valuable book for anyone intetrested in the applications of computer networks. Preface, Acknowledgements, Principles, Data Transmission, Protocols, Standards, Networks, Connections: X25 - ISDN and Private Circuits, Business Applications, Network Application - Electronic Mail, Network Application - File Transfer, Network Application - Electronic Data Interchange, Mobile Data Communications, Glossary, Index.